SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KARYAWAN BERPRESTASI DENGAN MENGGUNAKAN METODE ANALYTICAL HIEARARCHY PROCESS (Studi Kasus : PT.Capella Dinamik Nusantara Takengon) - Safitri, Kamalia; Waruwu, Fince Tinus; Mesran, Mesran (STMIK Budi Darma, 2017)
Employee is a supporting factor in a company, because with the existence of employees who have company qualification standards then the productivity of the company must be maintained and increasing. To obtain information quickly and accurately the achievement of appropriate employees meet the expected criteria, required a decision support system selection of outstanding employees. To know this, with a multi-criteria decision-making method by solving complex and unstructured situations into sections and arranging them in the hierarchy. By using Analytical Hierarchy Process (AHP) method on Decision Support System, the determination of achievement employees can be calculated based on the calculation of each criterion's weight, so it can select the employee achievement in the company quickly.